Discrete Wavelet Transform (DWT) Based Steganography Implementation - Gideon Adventus Simanungkalit; Daniel Syahputra Tarigan; Dinda Roulita Simangunsong (Jurnal Teknik Indonesia, 2023)
Steganography is the art of hiding information in a medium in such a way that its presence is undetectable by a third party. One of the techniques used in image steganography is the Discrete Wavelet Transform (DWT), which allows the decomposition of an image into different frequency sub-bands, thus facilitating data embedding without sacrificing visual quality. This paper discusses the manual calculation of the application of DWT in image steganography, including the image decomposition steps, the process of message embedding in a particular sub-band, and image reconstruction using the inverse DWT. Experimental results show that this method is effective in hiding information while maintaining good image quality.